MANAJEMEN PENDIDIKAN ISLAM DALAM TINJAUAN EPISTIMOLOGI - Hayatunnisa, St; Rohaemi, Rohaemi; Faruq Al-amini, Muhamad; Hidayat, Wahyu; Supardi, Supardi (STKIP Pesisir Selatan, 2023)
The process of establishing or managing an Islamic educational institution is known as Islamic education management. This process involves the use of human resources to institutional goals effectively and efficiently. In this case, epistemological philosophy serves as the basis for controlling Islamic education. The study aims to study the management of Islamic education using epistemology. This research uses a qualitative method of library study or literature study (Literature Review), and data is collected from related sources such as journals, e-books, or academic articles. The results of this study show that the management of Islamic education has a significant impact on Islamic educational institutions. The theory of Islamic education management practices refers to principles of governance that have not been fully implemented by Islamic educational institutions, such as the concept of transparency and integrity. Planning is regarded as a process or step of vital importance in achieving the objectives of an educational institution.